Conhecimento e conscientização: a historicidade do pensamento de Paulo Freire - Silva, Alexandre Rodrigo Nishiwaki da (2011)
Paulo Freire (1921-1997), Brazilian scholar, in his work develops the theoretical basis for the construction of educational liberating. The autonomy, the democratic relationships and the social changes are the theme of his reflections. Given this perspective, this work seeks to examine two fundamental concepts in Freire's work: knowledge and awareness. For this one seeks to articulate the thinking of Freire with the Brazilian historical context in an attempt to understand how the intellectual answer to the dictates of society in their educational approach. The first part of the paper examines the period extending from 1930 to 1964, which establishes the populist governments in Brazil, this time Freire begins his intellectual and pedagogical practice. Then we approach the years 1964 to 1985, a period known as the military dictatorship, in which the country faces hardened violent governments, Freire here are forced to leave the country and live in exile, during which develops a series of activities in different international bodies and produces several works in which consistently presents his ideas. Finally, we analyze the process of democratization of Brazil from 1985 to 1997, now returns to the country Paulo Freire and actively participates in several transformative initiatives. Along the way we strive to examine how the concept of knowledge and awareness become increasingly complex in the work of Paulo Freire following the historical development of Brazilian society, or keep itself historicity.